Alternative splicing for germ cell‐specific Mga transcript can be eliminated without compromising mouse viability or fertility. (14th September 2022) - Kitamura, Yuka; Suzuki, Ayumu; Uranishi, Kousuke; Nishimoto, Masazumi; Mizuno, Seiya; Takahashi, Satoru; Okuda, Akihiko
Abstract: The stimulated by retinoic acid gene 8 (STRA8)/MEIOSIN complex and polycomb repressive complex (PRC) 1.6, a PRC1 subtype, are believed to be positive and negative regulators of meiotic onset, respectively. During meiotic initiation, the transcription repressive activity of PRC1.6 must be attenuated so that meiosis‐related genes can be effectively activated by the STRA8/MEIOSIN complex. However, the molecular mechanisms that control the impairment of PRC1.6 function remain unclear. We recently demonstrated that the Mga gene, which encodes a scaffolding component of PRC1.6, produces variant mRNA by alternative splicing specifically during meiosis. Furthermore, the anomalous MGA protein encoded by the variant mRNA bears an intrinsic ability to function as a dominant negative regulator against the construction of PRC1.6 and is therefore assumed to be, at least in part, involved in impairment of the complex. Therefore, to unequivocally evaluate the physiological significance of Mga variant mRNA production in gametogenesis, we examined the consequences of a genetic manipulation that renders mice unable to produce Mga variant mRNA. Our data revealed that mutant mice were equivalent to wild‐type mice in terms of viability and fertility. Our detailed examination of spermatogenesis also revealed that this genetic alteration is not associated with any apparent abnormalities in testis size, spermatogenic cycle, timing of meiotic onset, or marker gene expression of spermatogonia and spermatocytes. Taken together, these data indicate that the production of germ cell‐specific Mga variant mRNA is dispensable not only for viability but also for gametogenesis. Abstract : PRC1.6, one of atypical PRC1, is known to function as a strong blockade against meiotic entry. Therefore, germ cells somehow need to impede the function of PRC1.6 to onset their meiosis. We recently demonstrated that germ cells produce an anomalous protein that functions as a dominant negative regulator against the construction of PRC1.6 from the Mga gene, which encodes a scaffolding component of PRC1.6, via meiotic stage‐specific alternative splicing. In this study, we examined the consequences of a genetic manipulation that renders mice unable to produce an anomalous MGA protein.